2010
DOI: 10.1143/jjap.49.015702
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Scanning Tunneling Microscopy Observation of Si(111) Surface Modified by Au+Ion Irradiation

Abstract: The real-time scanning tunneling microscopy (STM) observation of Au þ ion irradiation effects on a high-temperature Si surface has been performed using our original ion gun and STM combined system. Sequential STM images of a Si(111)-7Â7 surface kept at 500 C have been obtained before, during, and after Au þ ion irradiation with 3 keV. Vacancy islands, which are two-dimensional clusters of surface vacancies, and 5Â2-Au structures were formed on the sample surface, and their size were changed during the heat tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Acoustic microscopy [4] have revealed that vacancy islands tend to be formed at the step on silicon surface through segregation and coalescence of individual vacancies generated by sputtering. This phenomenon is observed in Si[111] [5] and in GaAs[110] surface [6] as well.…”
Section: Recently Goto Et Al Have Successfully Developed Amentioning
confidence: 76%
“…Acoustic microscopy [4] have revealed that vacancy islands tend to be formed at the step on silicon surface through segregation and coalescence of individual vacancies generated by sputtering. This phenomenon is observed in Si[111] [5] and in GaAs[110] surface [6] as well.…”
Section: Recently Goto Et Al Have Successfully Developed Amentioning
confidence: 76%
“…Whereas, Au atoms move toward the surface of the films after complete crystallization. When Au atoms are implanted into Si wafer by ion irradiation, the Au atoms reach the wafer surface almost without interacting with defects generated by the ion irradiation [14]. The migration of Au atoms was more prominently at high temperature.…”
Section: Resultsmentioning
confidence: 99%